2018
DOI: 10.3389/fpsyg.2018.00887
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Parental Burnout: Influence of Demographic Factors and Personality of Parents and Children

Abstract: Parental burnout is a syndrome related to parenthood and characterized by three dimensions: emotional and physical exhaustion, emotional distancing of parents from their children, and loss of parental accomplishment. Many factors can explain the interindividual differences in parental burnout (Roskam et al., 2017). In a study conducted among 372 French parents, we examined the relationship between parental burnout, demographic factors (age of parent and child(ren), age of parent at first birth, total number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
1
6

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 21 publications
6
73
1
6
Order By: Relevance
“…This burden could have increased due to the temporary closure of schools during the lockdown. In fact, being a young parent, being a first-time parent, having many children, or having infants has been reported as being a potential source of exhaustion and may lead to parental burnout (Vigouroux and Scola 2018 ). However, our results did not find any link between the number of children and the severity of distress symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This burden could have increased due to the temporary closure of schools during the lockdown. In fact, being a young parent, being a first-time parent, having many children, or having infants has been reported as being a potential source of exhaustion and may lead to parental burnout (Vigouroux and Scola 2018 ). However, our results did not find any link between the number of children and the severity of distress symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In the third hypothesis, we supposed low associations between parental burnout and sociodemographic variables. This assumption was based on previous findings (Le Vigouroux & Scola, 2018;Lebert-Charron et al, 2018;Lindström, Aman, & Lindhal-Norberg, 2011;Mikolajczak, Raes et al, 2018;Roskam et al, 2017Roskam et al, , 2018.…”
Section: The Current Studymentioning
confidence: 97%
“…Actually, research has already shown that some factors including the age of mothers (especially when the first child is born) and children, the number of children (Le Vigouroux & Scola, 2018;Mikolajczak et al, 2018b), the number and gender of caregivers (Mikolajczak et al, 2018b), having an adopted child (Denby, Rindfleisch, & Bean, 1999) or having children with disorders or diseases (Blanchard, Gurka, & Blackman, 2006;Lindström, Åman, & Norberg, 2011;Mousavi, 2020;Norberg, 2007), shorter length of the marriage (Mousavi, 2020), low level of mother's knowledge about parenting, poor perception of child's needs, a too high or too low sense of responsibility in mothers, the quality of the father's presence at home (Alikhani et al, 2013) all influence the risk of exhaustion in parents. However, personal factors such as low emotional intelligence, low parental self-efficacy beliefs, as well as some interpersonal factors such as poor parenting practices, lack of cooperation between parents, all play an even stronger role in parental burnout than sociodemographic factors (Mikolajczak et al, 2018b).…”
Section: Burnout In Parentsmentioning
confidence: 99%